2012
DOI: 10.1111/j.1743-6109.2011.02504.x
|View full text |Cite
|
Sign up to set email alerts
|

Tadalafil 2.5 or 5 mg Administered Once Daily for 12 Weeks in Men with Both Erectile Dysfunction and Signs and Symptoms of Benign Prostatic Hyperplasia: Results of a Randomized, Placebo-Controlled, Double-Blind Study

Abstract: Introduction Erectile dysfunction (ED) and lower urinary tract symptoms suggestive of benign prostatic hyperplasia (BPH-LUTS) commonly coexist in aging men. Tadalafil, a phosphodiesterase type 5 inhibitor approved for treating ED, is currently being evaluated for treating BPH-LUTS. Aims This multinational Phase 3 study assessed effects of tadalafil 2.5 or 5 mg once daily on ED and BPH-LUTS in men with both conditions during 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
148
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(160 citation statements)
references
References 22 publications
8
148
0
3
Order By: Relevance
“…[14][15][16] The results from these three Asian studies were also comparable with pivotal clinical studies of tadalafil in American and European men with BPH/LUTS. [17][18][19][20][21][22] The incidence/severity of BPH/LUTS has been shown to increase with increasing age; additionally, LUTS patients experience varying degrees of symptom severity, have comorbid conditions, or have prior exposure to BPH treatments, all of which might impact the efficacy of new therapies. [23][24][25] As individual studies, the three aforementioned trials were insufficiently powered to analyze patient subgroups.…”
mentioning
confidence: 99%
“…[14][15][16] The results from these three Asian studies were also comparable with pivotal clinical studies of tadalafil in American and European men with BPH/LUTS. [17][18][19][20][21][22] The incidence/severity of BPH/LUTS has been shown to increase with increasing age; additionally, LUTS patients experience varying degrees of symptom severity, have comorbid conditions, or have prior exposure to BPH treatments, all of which might impact the efficacy of new therapies. [23][24][25] As individual studies, the three aforementioned trials were insufficiently powered to analyze patient subgroups.…”
mentioning
confidence: 99%
“…18 Research among men with or without erectile dysfunction (ED) and LUTS has shown that tadalafil has a beneficial effect on LUTS independent of the drug's benefit on ED. [19][20][21][22][23] Indeed, a head-to-head comparison of tadalafil with the alpha-blocker tamsulosin showed similar improvements of LUTS due to BPH with each agent.…”
Section: Pde-5 Inhibitionmentioning
confidence: 99%
“…23 (A) Since iPDE5 is indicated for the treatment of erectile dysfunction, this class of medication may be an option in the treatment of patients presenting both disorders. 22,23,26 (A)…”
Section: Phosphodiesterase-5 Inhibitors (Ipde5s)mentioning
confidence: 99%
“…This indication is based on double-blind randomized placebo-controlled trials (RCT), that showed a significant reduction of I-PSS after twelve weeks. 22,23,26,27 (A) A prospective placebo-controlled study of tadalafil with tamsulosin used as an active comparator showed that tadalafil led to a decrease in tamsulosin-like I-PSS as early as week 1. 23 (A) Since iPDE5 is indicated for the treatment of erectile dysfunction, this class of medication may be an option in the treatment of patients presenting both disorders.…”
Section: Phosphodiesterase-5 Inhibitors (Ipde5s)mentioning
confidence: 99%
See 1 more Smart Citation